(untitled) (Research, Society and Development, 2021)
This paper presents reflections on the use of virtual classes as a strategy to guarantee students of Basic Education, in public education, the continuity of learning in the context of the pandemic of COVID-19. It was intended to understand the immediate impacts of remote education through digital tools. Considering specific characteristics of the state education network of the State of São Paulo, as well as the resources made available to students and teachers, based on practical reports, didactic strategies were analyzed using digital tools for teaching chemistry in high school classes. Thus, the qualitative approach was adopted, considering the records of the Google Classroom platform, in addition to bibliographic research. The study revealed the efforts of the São Paulo State Department of Education to make remote teaching possible, as well as the effort and difficulties faced by teachers and students, especially regarding digital access. Furthermore, it was observed the adoption of unusual strategies in the school context, such as the use of social networks and communication applications. It was concluded that the use of digital teaching and learning tools in Basic Education has positive aspects, such as enabling new ways of teaching and learning, favoring the use of different languages and students’ autonomy. The study suggests that the strategies adopted proved to be adequate to the emergency needs of remote education, however, the analyzes do not allow measuring the implications for effective learning, an aspect that may motivate other works.